An open-label, randomized, crossover study to assess anti-inflammatory effect of Simvastatin in Rheumatoid Arthritis statin-naïve patients with associated risk factors for cardiovascular disease - Greeff, O.B.W. (Oppel Bernhardt Wilhelm), 1948- (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.